Adenophora xiaoxiensis (Campanulaceae), an Endangered Species from China - Yi, Xin-Yu; Xie, Dan; Zhang, Cheng; Wang, Yu-Qin; Kang, Yong-Quan; Subedee, Bijay Raj; Zhang, Dai-Gui (Phytotaxa, 2019)
Adenophora xiaoxiensis (Campanulaceae), a new species from central China is described and illustrated. Molecular phylogenetic analysis (based on nuclear ribosomal ITS and the plastid regions trnL-F and matK) and morphology support recognition of A. xiaoxiensis as a distinct species sister to A. wilsonii. Adenophora xiaoxiensis has ovate-elliptic to broadly lanceolate cauline leaves with irregularly biserrate margins, triangular-ovate calyx lobes with 1-3 pairs subulate or linear teeth and a white corolla. About 70 individuals were observed in a restricted area of less than 100 m2. The habitat could be easily disturbed or destroyed, thus, we assessed it as endangered (EN), based on Criteria D of the International Union for Conservation of Nature Red List Categories.